2016
DOI: 10.3109/01612840.2016.1142623
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Connectedness Through Peer Training for Community-Dwelling Older People: A Person Centred Approach

Abstract: Social interaction and connectedness is important to the mental health and wellbeing of older people. The aim of this research study was to facilitate and increase opportunities for social connectedness for older people living in regional areas through the use of technology training. Weekly technology training sessions were conducted at a Seniors Citizen's Club with a peer trainer (an experienced, retired computer teacher) and sessions were attended not only by the six study participants, but also by other clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…While design of technology for the elderly needs to take into account their specific requirements, training is of particular importance in assisting with their acquisition of selfconfidence and continued use of the technology. Interestingly, the elderly do not like to be taught by younger people or their children and they recommend that these training environments should be led by older adults [50].…”
Section: Assistive Technology Devicesmentioning
confidence: 99%
“…While design of technology for the elderly needs to take into account their specific requirements, training is of particular importance in assisting with their acquisition of selfconfidence and continued use of the technology. Interestingly, the elderly do not like to be taught by younger people or their children and they recommend that these training environments should be led by older adults [50].…”
Section: Assistive Technology Devicesmentioning
confidence: 99%
“…Recent work in functional declines, not related to driving, have shown that improvements can be achieved, even for the very old . Furthermore, training in computing skills has been shown to have positive effects in quality of life outcome for community-dwelling older adults, many of whom are still driving (Burmeister, Bernoth, Dietsch, & Cleary, 2016). Although we understand the reasons for choosing to research the young-old, our interest in this review particularly concerns the oldest-old, which is the focus of our research (Eustace & Burmeister, 2013;Harvie, Burmeister, & Eustace, 2014.…”
Section: Reviewmentioning
confidence: 99%
“…Some research suggests that due to the severity of the disease, by the time a person is hospitalised it is too late to introduce technology; and that such technology only assists if it is already familiar to the person with dementia, through prior experience with it (Alzheimer Europe 2010; Burmeister et al 2016;Teipel et al 2016). Thus, restricting value considerations to hospital situations is too narrow for the following discussion.…”
Section: Introductionmentioning
confidence: 96%